Morphological and chemical variation of Stemona tuberosa from southern China – Evidence for heterogeneity of this medicinal plant species. (28th June 2017) - Chen, G.; Brecker, L.; Felsinger, S.; Cai, X.‐H.; Kongkiatpaiboon, S.; Schinnerl, J.
Abstract: The occurrence of bioactive alkaloids and tocopherols was studied in 15 different provenances of Stemona tuberosa Lour. collected in southern China, to examine chemical variation of individuals that show notable differences in flower characteristics. Morphological variations stimulated examination of chemical characteristics of these individuals. Methanolic root extracts of 15 individuals of S . tuberosa were comparatively assessed with HPLC‐UV‐DAD/ELSD. Five of seven compounds were co‐chromatographically identified. Two compounds were isolated and their structure elucidated using NMR and MS. Amounts of alkaloids and tocopherols were determined using HPLC‐UV‐DAD/ELSD with the external standard method. Five alkaloids, tuberostemonine (1 ), tuberostemonine A (2 ), neotuberostemonine (3 ), tuberostemonine N (4 ), stemoninine (5 ) and two 3, 4‐dehydrotocopherol derivatives were identified. Within S . tuberosa alkaloid accumulation tends either towards tuberostemonine (1 ) or stemoninine (5 ). All individuals show a notable co‐occurrence of compounds1 or5 and 3, 4‐dehydro‐δ‐tocopherol (6 ). These results coincide with differences in flower morphology of S . tuberosa . Stemona tuberosa, as defined in the Flora of China, shows a remarkable variation in flower morphology and additionally in the accumulation of alkaloids. The obtained data show the need for future species delimitation to either species or subspecies level.